2012
DOI: 10.1111/j.1365-2486.2012.02731.x
|View full text |Cite
|
Sign up to set email alerts
|

Thaw depth determines reaction and transport of inorganic nitrogen in valley bottom permafrost soils

Abstract: Nitrate (NO3 (-) ) export coupled with high inorganic nitrogen (N) concentrations in Alaskan streams suggests that N cycles of permafrost-influenced ecosystems are more open than expected for N-limited ecosystems. We tested the hypothesis that soil thaw depth governs inorganic N retention and removal in soils due to vertical patterns in the dominant N transformation pathways. Using an in situ, push-pull method, we estimated rates of inorganic N uptake and denitrification during snow melt, summer, and autumn, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
128
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(148 citation statements)
references
References 79 publications
(91 reference statements)
11
128
1
Order By: Relevance
“…DOC, DON and DIN are metabolized at variable rates (van Hees et al 2005, Harms and Jones 2012, and DOC and DON can sorb to mineral soil Asner 2001, Kawahigashi et al 2006), transform along surface and subsurface flow paths (Striegl et al 2005, Koch et al 2013, or accumulate in pore waters in poorly drained areas (Wickland et al 2007). Nevertheless, studies of permafrost-impacted ecosystems across the circumpolar region have documented changes in DOC and TDN consistent with our conclusion that near-surface permafrost soils can be important DOC and TDN sources upon thaw (Harms et al 2013, Abbott et al 2015, Loiko et al 2017, Keuper et al 2012, Wauthy et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…DOC, DON and DIN are metabolized at variable rates (van Hees et al 2005, Harms and Jones 2012, and DOC and DON can sorb to mineral soil Asner 2001, Kawahigashi et al 2006), transform along surface and subsurface flow paths (Striegl et al 2005, Koch et al 2013, or accumulate in pore waters in poorly drained areas (Wickland et al 2007). Nevertheless, studies of permafrost-impacted ecosystems across the circumpolar region have documented changes in DOC and TDN consistent with our conclusion that near-surface permafrost soils can be important DOC and TDN sources upon thaw (Harms et al 2013, Abbott et al 2015, Loiko et al 2017, Keuper et al 2012, Wauthy et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The production and transport of nitrogen in the active layer depends heavily 25 on the depth where flow is occurring. With increased depth the effect of denitrification is reduced which increases the net export of nitrogen (Harms and Jones, 2012). This phenomenon will particularly occur at sloping locations with high hydraulic gradient where the released nitrogen can be transported by water and supply nutrients to the low-lying wetlands in the arctic.…”
Section: Introductionmentioning
confidence: 99%
“…nitrogen sinks. Harms and Jones (2012) adopted this conceptual model, but applied 15 N at the base of the thaw layer by using a push-pull method. They also observed that nitrogen uptake occurred mostly during snowmelt in shallow soils with uptake rates significantly lower in summer and autumn, allowing for export of nitrogen from soils to lower lying wetlands or streams.…”
Section: Introductionmentioning
confidence: 99%
“…In continuous permafrost catchments, these factors are tightly linked: permafrost confines runoff and biological activity to the active layer and hydrologic processes exert a strong control on nutrient export dynamics (MacLean et al 1999;Stieglitz et al 2003;Townsend-Small et al 2011;Yano et al 2010;Harms and Jones 2012;Koch et al 2013;Harms and Ludwig 2016). The timing of TDN flux depends largely on runoff volume and the response to hydrological inputs in a catchment.…”
Section: Introductionmentioning
confidence: 99%
“…Runoff, which is needed to induce N transport (Perakis 2002), is influenced by catchment morphology, as the latter constitutes an underlying control on snow accumulation, hydrological flow paths and runoff response (Beven et al 1988;Ferguson 1999;Woo 2012). The composition of TDN exported also varies according to catchment morphology, as this regulates hydrological flow paths, soil moisture regimes, the reduction/oxidation state of soils, and hence N cycling processes (Pinay et al 2002;Petrone et al 2007;McNamara et al 2008;Yano et al 2010;Harms and Jones 2012;Abbott et al 2015;Harms and Ludwig 2016).…”
Section: Introductionmentioning
confidence: 99%